Municipal solid waste generation: an exploratory analysis of consumption patterns in Peru - Izquierdo Horna, Luis Antonio (2022)
Peru, a developing country, is experiencing an exponential increase in the municipal solid waste (MSW) generation due to population growth and disorderly territorial expansion in urban and rural areas. Most of these settlements do not have proper waste management, which causes contamination in various sectors: health, economy, environment (e.g., soil contamination, informal landfills), among others. Thus, this growth phenomenon can be explained through the consumption patterns of the population, especially those related to the household. To this end, this research seeks to contribute to the MSW management through an exploratory analysis using resources provided by public and non-governmental organizations. In this way, a national database was constructed that reflects consumption trends, characteristics, preferences and significant differences between rural and urban areas. It is expected that this information will contribute to the implementation of management tools that are better adjusted to reality in order to reduce the negative impacts generated by inadequate solid waste management.